The Quebec Task Force on Whiplash-Associated Disorders and the British Columbia Whiplash Initiative: A Study of Insurance Industry Initiatives - Robert W Teasell; Harold Merskey (Pain Research and Management)
Two studies on whiplash-associated disorders that were generated by insurance companies were reviewed. The Quebec Task Force (QTF) report was comprised of a cohort study, a best evidence synthesis and consensus recommendations. The British Columbia Whiplash Initiative (BCWI) propagated the QTF recommendations.